Biological Effects of Bone Marrow Concentrate in Knee Pathologies - Fortier, Lisa A.; Strauss, Eric J.; Shepard, David O.; Becktell, Liliya; Kennedy, John G. (The Journal of Knee Surgery, 2019)
With our aging population desiring to remain active, the incidence and costs associated with managing knee pain from both acute injury and symptomatic knee osteoarthritis continue to dramatically increase. Current treatment methods fall short with respect to their ability to improve the intra-articular environment and restore normal joint homeostasis. With increasing basic science and clinical evidence showing efficacy, cell-based therapies such as bone marrow concentrate (BMC) hold promise as a nonsurgical joint preserving treatment approach. BMC has inherent advantages over other treatments commonly used for various knee pathologies because it is a point-of-care orthobiologic product that uniquely and simultaneously delivers growth factors, anti-inflammatory proteins, and mesenchymal stem cells. There is increasing evidence for the use of BMC for repair of focal cartilage defects and for the treatment of generalized knee pain. However, continued high-quality studies are necessary for the clinical utility of BMC to be critically assessed with particular attention paid to appropriate patient selection, standardized aspiration, and processing and reporting of both functional and imaging-based outcomes.
Keywords: BMA; IRAP; BMC; MSC; IL-1ra